Consumer Protection Against Quantity and Price Fraud in MinyaKita Distribution - Mouna Suez Sianturi; Heru Sugiyono (JURNAL USM LAW REVIEW, 2025)
This study examines the legal liability of business actors and the effectiveness of consumer protection against double fraud practices in the distribution of MinyaKita cooking oil, involving both quantity reduction and pricing above the government-mandated Highest Retail Price (HET). The research employs a normative juridical method using statutory and case approaches, supported by limited institutional data from the Ministry of Trade, BPKN, and YLKI for corroborative purposes. The findings indicate that quantity manipulation and overpricing constitute violations of consumer protection law, legal metrology regulations, and trade policies, giving rise to business actors’ liability based on breach of contract, negligence, and semi-strict liability. Nevertheless, consumer protection remains ineffective due to regulatory overlap, weak distribution supervision, limited enforcement authority of the Consumer Dispute Settlement Board (BPSK), and low consumer legal awareness. The novelty of this study lies in its integrated analysis of consumer protection law, legal metrology, and distribution governance in addressing double fraud within a government-regulated commodity program. This study recommends strengthening BPSK’s authority, harmonizing regulatory frameworks, and enhancing distribution oversight and transparency to ensure effective and equitable consumer protection.